Driving Pressure Is Associated with Outcome during Assisted Ventilation in Acute Respiratory Distress Syndrome. (September 2019) - Bellani, Giacomo; Grassi, Alice; Sosio, Simone; Gatti, Stefano; Kavanagh, Brian P.; Pesenti, Antonio; Foti, Giuseppe
Editor's Perspective: What We Already Know about This Topic: Higher driving pressure during controlled mechanical ventilation is known to be associated with increased mortality in patients with acute respiratory distress syndrome. Whereas patients with acute respiratory distress syndrome are initially managed with controlled mechanical ventilation, as they improve, they are transitioned to assisted ventilation. Whether higher driving pressure assessed during pressure support (assisted) ventilation can be reliably assessed and whether higher driving pressure is associated with worse outcomes in patients with acute respiratory distress syndrome has not been well studied. What This Article Tells Us That Is New: This study shows that in the majority of adult patients with acute respiratory distress syndrome, both driving pressure and respiratory system compliance can be reliably measured during pressure support (assisted) ventilation. Higher driving pressure measured during pressure support (assisted) ventilation significantly associates with increased intensive care unit mortality, whereas peak inspiratory pressure does not. Lower respiratory system compliance also significantly associates with increased intensive care unit mortality. Background: Driving pressure, the difference between plateau pressure and positive end-expiratory pressure (PEEP), is closely associated with increased mortality in patients with acute respiratory distress syndrome (ARDS). Although this relationship has been demonstrated during controlled mechanical ventilation, plateau pressure is often not measured during spontaneous breathing because of concerns about validity. The objective of the present study is to verify whether driving pressure and respiratory system compliance are independently associated with increased mortality during assisted ventilation ( i.e ., pressure support ventilation). Methods: This is a retrospective cohort study conducted on 154 patients with ARDS in whom plateau pressure during the first three days of assisted ventilation was available. Associations between driving pressure, respiratory system compliance, and survival were assessed by univariable and multivariable analysis. In patients who underwent a computed tomography scan (n = 23) during the stage of assisted ventilation, the quantity of aerated lung was compared with respiratory system compliance measured on the same date. Results: In contrast to controlled mechanical ventilation, plateau pressure during assisted ventilation was higher than the sum of PEEP and pressure support (peak pressure). Driving pressure was higher (11 [9–14] vs . 10 [8–11] cm H2 O; P = 0.004); compliance was lower (40 [30–50] vs. 51 [42–61] ml · cm H2 O -1 ; P < 0.001); and peak pressure was similar, in nonsurvivors versus survivors. Lower respiratory system compliance (odds ratio, 0.92 [0.88–0.96]) and higher driving pressure (odds ratio, 1.34 [1.12–1.61]) were each independently associated with increased risk of death. Respiratory system compliance was correlated with the aerated lung volume (n = 23, r = 0.69, P < 0.0001). Conclusions: In patients with ARDS, plateau pressure, driving pressure, and respiratory system compliance can be measured during assisted ventilation, and both higher driving pressure and lower compliance are associated with increased mortality. Abstract : This study shows that in the majority of adult patients with acute respiratory distress syndrome, both driving pressure and respiratory system compliance can be reliably measured during pressure support (assisted) ventilation. Higher driving pressure measured during pressure support (assisted) ventilation significantly associates with increased intensive care unit mortality, whereas peak inspiratory pressure does not. Lower respiratory system compliance also significantly associates with increased intensive care unit mortality.Supplemental Digital Content is available in the text.